Gamma-ray irradiation differentially modulates PD-1 and CTLA-4 expression and tumour growth in parental and acquired radioresistant EMT6 mouse models - V Sham, Nur Fatihah; Hasani, Narimah Abdul Hamid; Hasbullah, Harissa Husainy; Wan Mohamad Zain, Wan Nor I’zzah; Hasan, Nurhaslina; Othman, Suraya; Osman, Nora Julianna; Abdul Karim, Muhammad Khalis; Syed Ahmad Fuad, Syed Baharom; Ibahim, Mohammad Johari (BiomedPress, 2026)
Background: Immune checkpoint proteins such as PD-1 and CTLA-4 play pivotal roles in tumour immune evasion. Our previous in vitro studies demonstrated upregulation of Pdcd1 and Ctla4 mRNA in the acquired radioresistant murine breast cancer cell line EMT6RR_MJI . This study aimed to evaluate their gene expression in vivo and assess the impact of gamma-ray irradiation on tumour progression. Methods: Two in vivo experiments were conducted using a mouse xenograft model subcutaneously implanted with either parental EMT6 or EMT6RR_MJI mammary carcinoma cells. In Experiment 1, levels of Pdcd1, Cd274, and Ctla4 mRNA were quantified by real-time PCR from tumours relative to control groups in both models. Mice in both control and treated groups were sacrificed on day 19 post-inoculation (5 days post-irradiation for treated groups), and tumour origin was validated by determining the expression of epithelial marker E-cadherin (Cdh1) and mesenchymal marker N-cadherin (Cdh2). In Experiment 2, tumour volume was measured weekly to assess treatment response relative to controls. Mice were sacrificed if they lost ≥10% of their body weight or showed signs of stress or ulceration. Results: Pdcd1 expression was significantly higher in EMT6RR_MJI tumours compared to parental EMT6 tumours (p<0.0001), with no significant difference observed for Ctla4. Gamma-ray irradiation reduced Pdcd1 expression in EMT6RR_MJI tumours (p<0.01) but not in EMT6. Conversely, Ctla4 expression increased significantly in irradiated EMT6 tumours (p<0.01) but remained unchanged in EMT6RR_MJI . Tumour growth was markedly faster in EMT6 tumours than in EMT6RR_MJI tumours from week 2 onward (p<0.0001). Irradiation significantly reduced tumour volume in EMT6 tumours at weeks 3 (p<0.01), 4, and 5 (p<0.001), while EMT6RR_MJI tumours showed no reduction. Conclusion: Gamma-ray irradiation differentially modulated Pdcd1 and Ctla4 expression in radioresistant (EMT6RR_MJI ) and parental (EMT6) tumour models. The absence of tumour reduction in EMT6RR_MJI tumours suggests inherent radioresistance. These findings provide preliminary insights into the link between immune checkpoint regulation and radiation response in breast cancer.